Health promotion for the oldest seniors in the social sector. Examples of policies and programmes from Poland and the Czech Republic (Epidemiology, Biostatistics, and Public Health, 2022)
The article identifies health promotion activities for the oldest people, who often become users of social services due to loss of capabilities, solitude and raising care needs related to worsening health status. The analysis is  based on the literature overview, experts’ consultations and interviews on the role of the social sector institutions in health promotion in selected countries. Examples of best practices in health promotion for older people in the social sector are presented. These include programmes of health information and campaigns on health risks avoidance, stimulation of physical activity, healthy eating for the oldest seniors, promotion of mental health and support of cognitive abilities, primary prevention activities and stimulation of social and cultural participation. The article concludes that health promotion activities for the oldest population, although on the side of main activities of the social sector, are an important element of activities of public and non-public institutions in providing care to dependent populations. Good practices identified typically involve numerous health promotion activities and require cooperation at the national – policy setting – level and within community.The article identifies health promotion activities for the oldest people, who often become users of social services due to loss of capabilities, solitude and raising care needs related to worsening health status. The analysis is  based on the literature overview, experts’ consultations and interviews on the role of the social sector institutions in health promotion in selected countries. Examples of best practices in health promotion for older people in the social sector are presented. These include programmes of health information and campaigns on health risks avoidance, stimulation of physical activity, healthy eating for the oldest seniors, promotion of mental health and support of cognitive abilities, primary prevention activities and stimulation of social and cultural participation. The article concludes that health promotion activities for the oldest population, although on the side of main activities of the social sector, are an important element of activities of public and non-public institutions in providing care to dependent populations. Good practices identified typically involve numerous health promotion activities and require cooperation at the national – policy setting – level and within community.